If It Pays, It Stays : Can Agribusiness Internalize the Benefits of Malaria Control? - Sedlmayr, Richard (Published by Oxford University Press on behalf of the World Bank, 2019)
Might a malaria control intervention entail agricultural effects that allow a commercial agribusiness to offset its costs? The randomized allocation of 39,936 insecticide-treated mosquito nets among 81,597 smallholder cotton farming households in 1,507 clusters helps evaluate this in the context of Zambia's cotton outgrowing industry. But despite large health impacts on treated households, no impact on cotton deliveries to the agribusiness is detected. With some caveats, the results tend to strike a discord with recent evidence on the agricultural productivity effects of malaria control.